An efficient scheme for sampling fast dynamics at a low average data acquisition rate. (25th January 2016) - Philippe, A; Aime, S; Roger, V; Jelinek, R; Prévot, G; Berthier, L; Cipelletti, L
Abstract: We introduce a temporal scheme for data sampling, based on a variable delay between two successive data acquisitions. The scheme is designed so as to reduce the average data flow rate, while still retaining the information on the data evolution on fast time scales. The practical implementation of the scheme is discussed and demonstrated in light scattering and microscopy experiments that probe the dynamics of colloidal suspensions using CMOS or CCD cameras as detectors.